Inter-municipal community network in the Aculco-El Oro tourist corridor as a strategy for cooperation and social cohesion - Mata-Arratia, Eduardo; Palmas-Castejón, Yanelli Daniela (Cooperativismo & Desarrollo, 2025)
The aim of this research is to analyse the creation of an inter-municipal community tourism network with the aim of unifying the Esplendor Mazahua Tourist Corridor, which includes the magical towns of Aculco and El Oro, located in the State of Mexico. Both municipalities complement each other because each has its own unique attractions, crafts, and cuisine, as well as other types of services depending on geographical conditions. The network aims to innovate in strengthening production chains and the internal committees of Pueblos Mágicos, as well as formulating regional development strategies, incorporating vernacular, empirical, and rational knowledge as key attributes for social cohesion. The study was carried out through participatory action research with a qualitative approach based on a bibliographic study, which was subsequently complemented by meetings with tourism service providers, using participant observation, interviews and a focus group approach. The main finding was that an inter-municipal tourism network could strengthen the region’s identity. To this end, it is necessary to consider cooperativism as a means of achieving regional development and mitigating common problems.